Review of the genus Stenothemus Bourgeois from Taiwan, with description of three new species (Coleoptera: Cantharidae) and additional distributional records of previously known species - Hsiao, Yun; Okushima, Yûichi; Yang, Ping-Shih (Zootaxa, 2016)
The genus Stenothemus Bourgeois from Taiwan is reviewed, with description of three new species: S. lupus sp. nov., S. gemini sp. nov. and S. vulpecula sp. nov. Each species is described with photos of habitus, and the new species also include illustrations of aedeagi, female genitalia and abdominal ventrite VII (= sternite VIII) of female if available. In addition, the female of S. mamorui Okushima & M. Satô, 1999 is described for the first time, and female genitalia and the abdominal ventrite VII are illustrated. A distribution map of Stenothemus from Taiwan is presented, and an updated key for the identification of Stenothemus species from Taiwan is given.